Tema Sentral Dakwah Qur'ani - Asep Muhyiddin (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2002)
Alquran is a legitimate and rich source of Islam that inspires ilmu dakwah its structure and development. Its viewpoints on human beings, universe, and God is especially revealing. It sees them as the three features which are closely related to the responsibility and accountability of human beings a both the servants and the agents of Allah on the earth.So far as dakwah concerns, the above perspective of Alquran bears three basic moral guidelines: dakwah with human and cultural orientations; dakwah with ecological orientations; and dakwah with theological orientations. These orientations depend solely on the qualification and comprehension of da'i (the subject of dakwah) about the principles of life as hinted in Alquran. This is why the task of da'i is not only appealing others but also being the first to practice the Islamic teachings.